The Role of Toeholds and Capital Gains Taxes for Corporate Acquisition Strategies - Federica Liberini; Antonio Russo; Michael Stimmelmayr (Center for Economic Studies and ifo Institute (CESifo), 2016)
Ownership takeovers often follow complex strategies where the control of the target firm is acquired through a sequence of independent contracts. Based on this observation, we develop a novel theoretical model wherein the acquiring firm decides on the number of steps towards the full ownership of the target (the acquisition structure) and on the combination of cash and stock used to finance the takeover (the method of payment). Within this framework, we analyze the effect of the capital gains tax on these two decision margins and test our theoretical prediction using a bivariate probit model on a sample of acquisition contracts between 2002 and 2014, collected from Bureau van Dijk's Zephyr database. Our estimates confirm the lock-in-effect and indicate a larger discouraging effect of rising capital gains taxes (+10%-points increase) on one-shot full acquisition (-6.0%-points) versus on sequential acquisitions (-5.2%-points). Further, we provide evidence that an increase in the capital gains tax (+10%-points) raises the probability of choosing one-shot full acquisition (+5.5%-points) instead of sequential acquisitions.
Keywords: C25; G34; G32; H25; D22; 330; merger & acquisition; sequential contract; toehold; capital gains tax; method of payment; lock-in effect